Pelatihan Pengolahan Data Penelitian Untuk Mahasiswa Jurusan Sosial Ekonomi Fakultas Pertanian Universitas Mataram - Setiawan, Rifani Nur Sindy; Eka Nurminda Dewi Mandalika; Anna Apriana Hidayanti; Ni Made Nike Zeamita Widiyanti; Kusuma, Wirajaya (Universitas Mataram, 2025)
Abstract: This community service activity aims to improve the ability of students of the Socioeconomics Department, Faculty of Agriculture, University of Mataram in processing research data using Statistical Package for the Social Sciences (SPSS) software. The target of this activity is final semester students who are or will be compiling their final assignments, where mastery of data analysis is a crucial aspect. The method used is training with a direct practice approach and case studies. To measure the effectiveness of the activity, a pretest and posttest were conducted related to basic statistical knowledge and the use of SPSS. The results of the training showed a significant increase (p-value = 0.000 <0.005) in the understanding and skills of participants in processing research data. This activity makes a real contribution to improving students' readiness in compiling their final assignments independently and systematically.